1983
DOI: 10.3171/jns.1983.58.6.0799
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of the neurologically disabled patient: principles, practice, and scientific basis

Abstract: Rehabilitation is a therapeutic program specifically directed toward restoring the optimum level of function available to patients with severe permanent disabilities. It complements standard care, which focuses on curing the primary pathology. Preventive rehabilitation is designed to minimize the complications of inactivity that tend to develop during a protracted curative process (contractures, pressure sores, muscle atrophy, cardiopulmonary deconditioning, cognitive dulling). Comprehensive rehabilitation foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…4,5 Early recovery of muscle strength post-ISCI has been identified as a useful predictor of ambulatory capacity. For example, Waters et al 6,7 reported that lower extremity motor recovery 1 month post-injury was a good predictor of whether an individual became a community ambulator at 1-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Early recovery of muscle strength post-ISCI has been identified as a useful predictor of ambulatory capacity. For example, Waters et al 6,7 reported that lower extremity motor recovery 1 month post-injury was a good predictor of whether an individual became a community ambulator at 1-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study has shown that physical activity stimulates neurogenesis in the adult hippocampus (van Praag et al ., 1999). Repetitive neuromuscular activity also has therapeutic value for improving locomotor ability following trauma in animals (Burgess & Villablanca, 1986; Barbeau & Rossignol, 1987; Edgerton et al ., 1991; Stummer et al ., 1995), and humans (Perry, 1983; Wernig et al ., 1995; Harkema et al ., 1997). Therefore, it is possible that managed physical activity can be used to induce trophic factors in selective networks with beneficial effects for neuronal plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…This inactivity-induced muscle atrophy results in a decrease in muscle force-generating capacity and increases the risk for subsequent health problems such as bone fractures, osteoporosis, and increased risk of falls (7,16,25). Therefore, understanding the signaling pathway(s) responsible for disuse muscle atrophy is an important first step toward developing a therapeutic approach to delay or prevent skeletal muscle atrophy.…”
mentioning
confidence: 99%